THE CRIMINAL JUSTICE SYSTEM IN INDONESIA: CHALLENGES AND EFFORTS TO ACHIEVE JUST LAW ENFORCEMENT - Tatang Sholahudin; A. Hendro Yulianto; Hartanto (International Peneliti Ekonomi, Sosial dan Teknologi, 2026)
The Indonesian Criminal Justice System is an integrated mechanism involving the Police, Prosecutor's Office, Courts, and Correctional Institutions in enforcing criminal law. This system functions not only to combat crime but also to achieve justice, legal certainty, and the protection of human rights. However, in practice, the Indonesian criminal justice system still faces various challenges, such as weak coordination among law enforcement officials, low integrity among law enforcement officials, overcrowding of correctional institutions, and the increasing complexity of technology-based crimes. This study aims to analyze the challenges facing the Indonesian criminal justice system and examine efforts that can be made to realize just law enforcement. The research method used is normative legal research with a statutory and conceptual approach. The results show that optimization of the criminal justice system can be achieved by strengthening the integrity of law enforcement officials, improving coordination between institutions, implementing Restorative Justice, and utilizing technology in the judicial process. Thus, criminal justice system reform is needed that is not only oriented towards legal certainty but also ensures the achievement of substantive justice for the community.